A Bibliometric Study of Research Patterns in National Income and Economic Growth, 2015–2024 - Aprilia, Novita; Subroto, Waspodo Tjipto; Sakti, Norida Canda (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to examine the evolution of national economic development and infrastructure research from 2015 to 2024. The research data used are those that have been published in scholarly journals that are indexed by Scopus. Data extraction results are derived from 239 documents. Results of research on the topic of national development and economic stagnation indicate that the number of trains is rather unstable. However, research on the national economy and building boom increased from 2015 to 2016 and experienced a decline in 2017. However, from 2017 to 2019 there was another decline in growth, and from 2019 to 2020 there was another decline in growth. The final year of the trend was 2020 to 2023 there was a slight decline in growth, but from 2023 to 2024 there was a further decline in growth. The results of the study on the Rodriguez-Pose domain show that there are four clusters that have been identified